Prospective evaluation of the clinical utility of endoscopic submucosal dissection (ESD) in patients with Barrett’s esophagus: a Western center experience - Coman, Roxana M.; Gotoda, Takuji; Forsmark, Christopher E.; Draganov, Peter V. (Endoscopy International Open, 2016)
Background and study aims: Endoscopic submucosal dissection (ESD) carries significant advantages over endoscopic mucosal resection. As such, ESD is an established therapy for esophageal squamous cell carcinoma but there are only limited data on ESD as therapy for Barrett’s esophagus (BE). Thus, we prospectively evaluated the outcomes of ESD in patients with BE with high-grade dysplasia (HGD) and early esophageal adenocarcinoma (EAC) performed in a Western center. Patients and methods: This is a prospective cohort study. Indications for ESD included: (1) early EAC defined as lesions with intramucosal cancer or superficial submucosal invasion; (2) early EAC with positive lateral margin after EMR; and (3) nodularity with HGD that could not be removed en-bloc with EMRResults: From October 2013 to July 2015, 36 consecutive patients (median age 69, 32 males) underwent ESD at our center. Median procedure time was 88 minutes, with median maximal diameter of resected specimens of 49 mm. En-bloc, R0, and curative resection rates were 100 %, 81 %, and 69 %, respectively. Intramucosal EAC was found in 13 patients (36 %), and submucosal invasion in 13 patients (36 %). In 59 % of the cases, there was discrepancy in the pre- and post-ESD histopathologic diagnosis.Adverse events occurred in 8 patients (22 %), including one episode of bleeding treated with endoscopy and seven esophageal strictures, which were successfully managed with dilations. Conclusions: ESD for BE with HGD/early EAC is feasible and safe with resulting very high en-bloc and R0 resection rates. ESD provided for more accurate pathologic evaluation and significant discrepancy between the pre- and post-ESD histopathological diagnosis was noted.